Facing the mountain : a true story of Japanese American heroes in World War II - Brown, Daniel James, 1951- (Viking, an imprint of Penguin Random House LLC, 2023)
Adapted for young readers from the New York Times bestseller by Daniel James Brown, Facing the Mountain is the remarkable true story of three brave Japanese American soldiers who fought for the United States during World War II while facing discrimination at home. Perfect for readers of The Boys in the Boat.